The Drosophila accessory gland as a model for prostate cancer and other pathologies - Wilson, C; Leiblich, A; Goberdhan, D; Hamdy, F (Elsevier, 2016)
The human prostate is a gland of the male reproductive tract, which together with the seminal vesicles, is responsible for most seminal fluid production. It is a common site of cancer, and unlike other glands, it typically enlarges in ageing men. In flies, the male accessory glands make many major seminal fluid components. Like their human equivalents, they secrete proteins from several conserved families, including proteases, lectins and cysteine-rich secretory proteins, some of which interact with sperm and affect fertility. A key protein, sex peptide, is not conserved in vertebrates, but plays a central role in mediating long-term effects on females after mating. Although post-mitotic, one epithelial cell type in the accessory glands, the secondary cell, continues to grow in adults. It secretes microvesicles called exosomes from the late endosomal multivesicular body, which after mating, fuse with sperm. They also appear to affect female post-mating behaviour. Remarkably, the human prostate epithelium also secretes exosomes, which fuse to sperm in vitro to modulate their activity. Exosomes from prostate and other cancer cells are increasingly proposed to play fundamental roles in modulating the tumour microenvironment and in metastasis. Here we review a diverse accessory gland literature, which highlights functional analogies between the male reproductive glands of flies and humans, and a critical role for extracellular vesicles in allowing seminal fluid to promote male interests within the female. We postulate that secondary cells and prostate epithelial cells use common mechanisms to control growth, secretion and signalling, which are relevant to prostate and other cancers, and can be genetically dissected in the uniquely tractable fly model.